FACTORS INFLUENCING THE LEVEL OF USE OF CLIMATE SMART AGRICULTURAL PRACTICE (CSAP) IN SOKOTO STATE, NIGERIA - OJOKO, EMMANUEL ADA; Akinwumi, James A.; Yusuf, Sulaiman A.; Oni, Omobowale A. (Journal of Agricultural Sciences (Belgrade), 2017)
ABSTRACT Climate Smart Agriculture (CSA) is paramount to the success of farming activities today in the face of the menace of climate change. This study therefore investigates the frequency of usage of CSA and the factors influencing its level of usage in the Northern agricultural zone of Sokoto State. A well-structured questionnaire was used for data collection. The data used for the analysis are cross sectional data collected from 120 rural farming households in six (6) villages across two (2) local government areas. Descriptive statistics, Adaptation Strategy Use Index (ASUI) and Ordered probit regression model were used for data analysis. Results indicated that majority of the respondents are male (83.33%), married (83.33%), have Quranic education (73.33%), household size of 1-10 persons (58.33%), farming experience of 16–30 years (49.17%) and are between the ages of 46-60 years (44.17%). Also, the practice of conservation agriculture is the most used CSAP in the study area, while the results of the ordered probit regression showed that years of education and membership of a social group are significant explanatory variables influencing the level of use of CSAP among the low user and high user categories at 10% and 1% level of significance respectively, while access to credit significantly influences only the low user category at 10% level of significance. The study therefore concludes that CSAP is being practiced at different levels in the study area with various factors influencing their usage, and therefore recommend that the farming households be well enlightened by extension agents on the benefits of CSAP.